Security Guards and Counter-terrorism: Tourism and Gaps in Terrorism Prevention - Howie, Luke (The international journal of religious tourism and pilgrimage, 2014)
Organisation operating in the tourism industry are high priority targets for terrorists. In the aftermath of the 9/11 attacks tourism destinations, hotels and modes of public transportation have regularly been targeted by terrorists seeking to convey their violent message. As such, leaders and managers in the tourism industry carefully plan their security and counter-terrorism responses, often involving the hiring of security guards. It is here that I believe a significant gap in counter-terrorism preparedness exists. I argue that protecting tourism destinations is only possible if consideration is given the effectiveness of security guards and understanding that their well-being will impact upon their ability to deliver security. I want to draw attention to the often ignored social role of security guards. On 9/11, 42 security guards died whilst helping save the lives of thousands. They performed their jobs admirably, despite being low-paid, under-appreciated workers. In this paper I explore the social role of security guards in the context of tourism security. By drawing on representations of security guards in popular culture and reports on the state of the security guard industry. I argue that the lack of attention on the quality and well-being of guards is a significant black-spot in tourism security and terrorism preparedness